IMPLEMENTASI PASAL 5 PERATURAN MENTERI PERHUBUNGAN NOMOR 45 TAHUN 2020 TENTANG KENDARAAN TERTENTU DENGAN MENGGUNAKAN PENGGERAK MOTOR LISTRIK (Studi Di Jalan Jenderal Ahmad Yani Pontianak) - NIM. A1012201045, LEVI THOMYUSTIN (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac From Article 5 of the Minister of Transportation Regulation Number 45 of 2020 concerning Certain Vehicles Using Electric Motor Drives, that on Jalan Jenderal Ahmad Yani Pontianak they do not allow electric bicycle riders to ride their vehicles on the sidewalk and also on the sidewalk there is a bicycle lane which in Article 5 Regulation of the Minister of Transportation Number 45 of 2020 concerning Certain Vehicles Using Electric Motor Drives regulates the places that have been provided and these places are bicycle lanes and sidewalks on Jalan Jenderal Ahmad Yani Pontianak. But in reality, electric bicycles are prohibited from being ridden in these areas which are considered inadequate. To avoid violations so that people do not ride electric bicycles in this area, notice boards have been installed so that people do not violate these rules.So the author formulates the problem as follows: